Posthumanism as a Mode of Problematization and Enhancement of Humanism - Jelica A. Veljović (University of Belgrade, 2019)
The main objective of the present work is to concisely, descriptively and comparatively present the fundamental concepts, perspectives and postulates of the contemporary posthumanist theories. Besides these observations, the paper also aims to express and maintain a critical scope of all the posthumanist tendencies developed till present day, starting from non-modern and antimodern, and passing to the transhumanism and critical posthumanism. At the beginning of the paper there is an outlook on the origins and development of the posthumanism, dating it back to the deconstruction and poststructuralist philosophy and relating it to the technological improvement of the human society. Due to the paper’s critical approach to the posthumanist phenomena different representations of human and his environment will be taken into account, especially when it comes to categories such as cyborg, virtual reality and cyber-culture. At the end of the paper, all of these diverse and yet complementary posthumanist concepts and perspectives will be displayed through their presence in the framework of literature, which is conceived as one of the primary fields for creating and investigating the future of humanity. Related to this, it will be analyzed the relation between posthumanism and cyber-punk literary genre, and concepts such as ergodic literature, cyber-text and information narrative. As a matter of conclusion, the paper brings out the stances of the representative theoreticians of critical posthumanism, who focus on the establishment of new ethical and aesthetical fundaments of the new humanism, taking also into consideration the radical reform of the academic field of humanities as well.